From somewhere out there - Dass, Karthika; Mitra, Ankur (New Delhi Children's Book Trust, 2009)
A little girl falls down a rabbit hole and discovers a world of nonsensical and amusing characters.
Keywords: Science fiction -- Juvenile fiction